2022
DOI: 10.1111/lam.13719
|View full text |Cite
|
Sign up to set email alerts
|

Exometabolomic analysis of susceptible and multi-drug resistant Pseudomonas aeruginosa

Abstract: Significance and Impact of the Study: Despite numerous efforts to clarify genotypic differences between antimicrobial resistant and susceptible Pseudomonas aeruginosa isolates, few studies addressed differences in metabolism of clinically important pathogens. To our knowledge, there has been no report on extracellular metabolite characterization of susceptible and resistant strains of P. aeruginosa. This study provides insights into a metabolic footprint of MDR and susceptible P. aeruginosa clinical isolates i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Notably, exogenous myo-inositol has been associated with amplified sensitivity of Aeromonas hydrophila to florfenicol (Zhao et al, 2018). Further studies have corroborated that the extracellular levels of palmitic and oleic acids in antibiotic-sensitive strains considerably surpass those in multi-drug resistant counterparts (Kocak et al, 2022). In addition, glutamate is a crucial component in the synthesis of glutathione.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Notably, exogenous myo-inositol has been associated with amplified sensitivity of Aeromonas hydrophila to florfenicol (Zhao et al, 2018). Further studies have corroborated that the extracellular levels of palmitic and oleic acids in antibiotic-sensitive strains considerably surpass those in multi-drug resistant counterparts (Kocak et al, 2022). In addition, glutamate is a crucial component in the synthesis of glutathione.…”
Section: Discussionmentioning
confidence: 96%
“…It is important to note that this present study also found significant increased glycerol 3-phosphate and sphingosine in the extracellular metabolites after CRAMP-34 treatment. Glycerol 3-phosphate is the key precursor to build membrane lipids, and sphingosine is involved in the synthesis of sphingolipids which is a class of cell membrane lipids ( Kocak et al., 2022 ). It is speculated that the CRAMP-34 may cause the destruction of bacterial cell membrane, thereby stimulating the massive synthesis of new bacterial cell membranes.…”
Section: Discussionmentioning
confidence: 99%
“…The de-phosphorylated form, trehalose, can serve as a carbon source but also has an important role in bacteria during osmotic stress ( 61 , 62 ). The presence of extracellular trehalose has been found to be significantly associated with MDR P. aeruginosa isolates, compared to susceptible isolates ( 63 ). Ultimately, the signaling pathways that regulate trehalose (and thus trehalose 6-phosphate) in osmotic and other stress-response pathways are currently undefined ( 62 ).…”
Section: Discussionmentioning
confidence: 99%